AD, Volume 3, n° 4, 1978 - Full Issue (Africa Development, 1978)
Contents ARTICLES Abdalla S. Bujra Editorial : CODESRIA and Social Science in Africa .............................. 5 CODESRIA et Sciences Sociales en Afrique ......................13 Samir Amin - C. Atta-Mills - A. Bujra - G. Hamid et T. Mkandawire Social Science and the Development Crisis in Africa : Problems and Propects ........................ 23 F. Yachir Recherche Economique et Système Mondial Capitaliste : le Tiers Monde et l'Instrumentalisation de la Recherche ............... 47 Summary .................... 63 P. Anyang Nyong'o The Teaching of Social Sciences in East Africa ......................... 65 Résumé ........................ 83 M. Diouf Les Sciences Sociales en Afrique de l'Ouest Francophone .......................... 85 Summary .......................... 101 G. C. K. Gwassa The Role of Research Institutes in Socialist States in Africa ..................... 103 Résumé ............................. 108 J. Pegatienan Hiey Le Rôle des Institutions de Recherche dans les Pays Africains à Economie de Marché, le Cas du Centre Ivoirien de Recherche Economiques et Sociales, Université d'Abidjan ...................... 109 W.M. Senga and S.E. Migot Adholla Social Science Research and National Development in Kenya : The Case of the Institute for Development Studies, University of Nairobi ...............................123 Samir Amin A propos du Nouvel Ordre Economique International et de l'Avenir des Relations Economiques Internationales ................ 133